PECULIARITIES OF TEACHING COMPREHENSIVE LISTENING TO DIGITAL STUDENTS - Borisova, Inna; Balabas, Natalya (Revista Inclusiones, 2020)
This article deals with searching for effective ways of developing Bachelor and Master students’ listening skills in conditions of all-round digitalization of the human society. Relying on traditional approaches to teaching comprehensive listening, the authors develop some original postulates helping them remove the barriers hindering this process. The presented research is relevant due to the introduction of new educational standards adopted in Russia after its joining the Bologna process. The creation of the unified educational space and the country’s inclusion into the globalization process demand such transferable skills as intercultural sensitivity, managing uncertainty, the ability of adjusting communication to local styles and building relationships between people from different cultures. To be competitive in their academic and professional fields, students should get aligned with all these changes and demands. Keeping this in view, the authors try to customize the teaching-leaning process to the peculiarities of young people who cannot do without different gadgets involving them in virtual reality and dictating them the corresponding way of thinking. The article is supplemented with charts and graphs demonstrating the intermediate results obtained by the researchers. However, they stress the fact that the society digitalization is still going on, and today’s teachers are not just third-party observers, but rather direct participants of the processes under investigation. That is why, registering some positive shifts, one can hardly draw unambiguous conclusions at this stage of research.